The influence of intergenerational relationships on depressive symptoms in elderly patients with multiple chronic conditions: the mediating roles of self-rated health and well-being - Wenjia Feng; Pengxin Geng; Huaiju Ge; Qianqian Gao; Weiqin Cai; Qi Jing; Runguo Gao; Anning Ma (BMC Public Health)
Abstract Background The superimposition of multiple chronic conditions places a heavy physical burden and life pressure on older adults, making them more prone to psychological distress and significantly increasing their risk of depression, which has become an urgent public health issue. Intergenerational relationships, as the main source of social support for older adults, have a profound effect on their mental health. This study aims to explore the potential mediating mechanisms by which intergenerational relationships influence depressive symptoms among older adults within the context of the Chinese “filial piety” culture, providing a theoretical foundation for optimizing intergenerational support and improving the psychological well-being of older adults. Methods Data from the 2020 China Family Panel Study (CFPS) were used, and 739 elderly patients with multiple chronic conditions were selected as the study subjects. Data on intergenerational relationships, self-rated health, well-being, and depressive symptoms were also obtained. A chain mediation model was developed using SPSS PROCESS macro model 6, and one-way ANOVA, Pearson correlation analysis, and mediation effect tests were performed to investigate the effects of intergenerational relationships, self-rated health, and well-being on depressive symptoms in elderly patients with multiple chronic conditions. Results Intergenerational relationships, self-rated health, and well-being were found to be significantly correlated with depressive symptoms (P < 0.05). Intergenerational relationships negatively predicted depressive symptoms (β = -0.610, P < 0.01). Self-rated health (β = -1.115, P < 0.001) and well-being (β = -0.653, P < 0.001) mediated the effect of intergenerational relationships on depressive symptoms. Additionally, self-rated health and well-being were identified as chain mediators in this relationship for elderly patients with multiple chronic conditions (β = -1.118, P < 0.001). Conclusion Intergenerational relationships can reduce depressive symptoms among elderly patients with multiple chronic conditions by enhancing self-rated health and well-being. These findings highlight the importance of family support and emotional communication in mental health interventions for older adults. Therefore, healthcare professionals should incorporate family support and encourage positive intergenerational relationships when designing interventions to foster a supportive environment and improve quality of life.